A multi-objective approach for the trajectory planning of a 7-DOF serial-parallel hybrid humanoid arm - Wang, Zesheng; Li, Yanbiao; Sun, Peng; Luo, Yiqin; Chen, Bo; Zhu, Wentao (Mechanism and machine theory, 2021)
•Inspired by the human arm, a 7-DOF redundant hybrid humanoid arm is proposed.•Dynamic full solutions are obtained by equilibrium and deformation equations.•Based on the normalized Jacobian condition number, an optimal path is obtained by using GA.•The trajectory, interpolated by quintic B-splines, is optimized with NSGA-II.•The manipulator can work with lower energy and higher stability through the proposed method. Humanoid robots are an elusive long-term goal in robotics, and a humanoid arm is an essential actuator. Inspired by the motion characteristics of the human arm, a seven-degree-of-freedom (DOF) serial-parallel hybrid humanoid robotic arm is proposed. With the mechanism as an example, a solution of multi-objective trajectory planning is addressed using an indirect method to execute a point-to-point mission with faster time, lower energy and higher stability. First, to avoid abrupt changes of the joint angle, the path with a better joint-rate distribution is gained based on normalized Jacobian condition number. On the basis of this path, a multi-optimization model considering travelling time, energy consumption and torque fluctuation is formulated to plan the trajectory interpolated by quintic B-splines. The elitist non-dominated sorting genetic algorithm (NSGA-II) is used to address the model, and the optimal solution is determined by defining the weight value of the objective. Then, the complete dynamic model is obtained by combining equilibrium and deformation coordination equations. Finally, compared with another important trajectory planning methodology, the feasibility and effectiveness of the proposed methodology are validated through numerical simulations.